Scale-dependent responses to environmental fluctuations in tropical tree species’ crown temperatures - Shannon L. J. Bayliss; Eben N. Broadbent; Angélica M. Almeyda Zambrano; Susan Cordell; Stephanie Pau (Communications Earth & Environment)
Abstract Tropical forests may be nearing critical temperatures, yet tree species may respond differently. Using high-resolution thermal, hyperspectral, and LiDAR imagery, we mapped 652 crowns of four Hawaiian tree species to study the effects of crown traits and abiotic conditions on species’ temperatures at two scales (whole crown vs. sunlit leaves). We show scale-dependent, species-specific relationships with environmental fluctuations. Net radiation was consistently the dominant determinant of crown temperature deviations from air temperature (Tdiff), while vapor pressure deficit, wind speed, and crown traits (e.g., roughness) varied in importance by species and scale. Species explained 17% and 44% of Tdiff variation at the crown and leaf scales, respectively, after controlling for climatic factors. Findings suggest that leaf temperatures overestimate larger-scale temperature differences, while canopy-scale observations underestimate leaf heat stress. Because leaf and crown traits can have opposing effects on Tdiff, disentangling these can advance our understanding of species’ thermoregulation under climate change.